Effects of pregnancy in feedlot heifers on performance and carcass characteristics - Bishop, G.L.; Brethour, J.R.; Marston, T.T.; Lawrence, T.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty-eight, spring-born, yearling heifers were raised, estrous synchronized, artificially inseminated once, and then finished at the Kansas State University Western Kansas Agricultural Research Center at Hays to determine the effects of pregnancy status on feedlot performance and carcass traits. To achieve a common endpoint at slaughter, heifers were allotted to one of two slaughter dates to achieve a backfat measurement of 0.5 inch. Therefore, both open and pregnant heifers were slaughtered at either 105 or 147 days (fetal age averaged 174 days for the pregnant heifers). Initial weight, rate of gain, and final weight were similar between open and pregnant heifers (P>0.36). Dressing percentage and ribeye area were lower (P<0.05) for pregnant than open heifers. Hot carcass weight tended (P=0.13) to be greater for open heifers. No differences between treatment groups were observed for fat thickness, percentage kidney, pelvic, and heart fat, yield grade, marbling score, or maturity score (P>0.16). However, even though only small differences were recorded in carcass weights, yield grades, and quality grades, their impact on carcass value and cattle feeding profits may be important.
Keywords: Beef; Pregnancy; Heifers; Performance; Carcass characteristics